2019
DOI: 10.1136/bmjopen-2019-029717
|View full text |Cite
|
Sign up to set email alerts
|

The impact ofInfection Prevention and control (IPC) bundle implementationon IPC compliance during the Ebola virus outbreak in Mbandaka/Democratic Republic of the Congo: a before and after design

Abstract: ObjectivesTo assess the impact of refresher training of healthcare workers (HCWs) in infection prevention and control (IPC), ensuring consistent adequate supplies and availability of IPC kits and carrying out weekly monitoring of IPC performance in healthcare facilities (HCFs)DesignThis was a before and after comparison studySettingsThis study was conducted from June to July 2018 during an Ebola virus disease (EVD) outbreak in Equateur Province in the Democratic Republic of the Congo (DRC).Participants48 HCFsI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 8 publications
1
10
1
Order By: Relevance
“…Similar findings have been reported in other West African countries [21,28]. Surprisingly, this gap does not seem to translate into a lack of [29]. We found that rural areas where significantly less HCW had received IPC training than in the urban areas reported higher scores on certain topics regarding practices.…”
Section: Discussionsupporting
confidence: 82%
“…Similar findings have been reported in other West African countries [21,28]. Surprisingly, this gap does not seem to translate into a lack of [29]. We found that rural areas where significantly less HCW had received IPC training than in the urban areas reported higher scores on certain topics regarding practices.…”
Section: Discussionsupporting
confidence: 82%
“…Surprisingly, this gap does not seem to translate into a lack of knowledge or deficient practices towards VHF. A recent study on IPC in the DRC suggested that a higher quantity of HCW with IPC training does not increase IPC performance of healthcare facilities [29]. We found that rural areas where significantly less HCW had received IPC training than in the urban areas reported higher scores on certain topics regarding practices.…”
Section: Resultscontrasting
confidence: 42%
“…A study in the 2018 DRC Equateur outbreak [ 41 ] demonstrated the importance of refresher training of health care workers in IPC practices. After the training, compliance with protocols was significantly improved at rural health centres as well as at district hospitals.…”
Section: Resultsmentioning
confidence: 99%